Cyberbullying and the Effect on School Climate - Waterstreet, Derek J. (My University, 2012)
Cyberbullying, defined as the willful and repeated harm through the use of computers, cellphones, and other electronic devices, has increasingly caused problems with a school's quality and character, otherwise known as the school's climate. This study examined the relationship between a school's climate and the presence of cyberbullying within a school.
Color poster with text, images, and graphs.
Keywords: Cyberbullying; Bullying in schools; School environment--Social aspects; Posters